Conversion factors for effective dose and organ doses with the air Kerma area product in hysterosalpingography. (January 2021) - D'Alessio, Andrea; Cannillo, Barbara; Guzzardi, Giuseppe; Cernigliaro, Massimiliano; Carriero, Alessandro; Brambilla, Marco
Highlights: The prefiltration has a significant impact on effective dose when high as in most modern angiographic equipment. The algorithm for deriving E from KAP uses conversion factors which depend on the amount of copper filtration in the X-ray system. The algorithm provides accurate estimates of effective and organ doses in HSG. The functional form of the algorithm does not depend on the type of interventional procedure. Abstract: Histerosalpingography (HSG) remains the dominant diagnostic tool for investigation of infertility in women. Conversion factors used to estimate effective (E) and organ doses (HT ) from air Kerma area product (KAP) are needed to estimate patient doses in HSG, performed with state-of-the-art fluoroscopic X-ray systems with digital detectors. In this study, estimates of E and HT for six critical organs/tissues, were derived on an individual basis in 120 HSG procedures and in 1410 irradiation events, performed on two X-ray systems from information available through the radiation dose structured report using Monte Carlo methods. Mean values of E and Hovaries were1.0 ± 0.9 mSv and 5.6 ± 5.4 mGy. E/KAP conversion factors of 0.13; 0.18; 0.28 and 0.35 mSv Gy −1 cm −2 were established for irradiation events with a Cu filtration of 0.0; 0.1; 0.4 and 0.9 mm. A high agreement was obtained between E estimated through Monte Carlo methods and E/KAP conversion factors accounting separately for the different modes of fluoroscopy and the radiography component of HSG, with a systematic error of 0 mSv and lower/upper limits of agreement of −0.6 and 0.5 mSv. On the contrary, the use of a single coefficient of conversion did not provide accurate estimates of E, showing a bias of −0.4 mSv and lower and upper limits of agreement of −1.9 and 1.2 mSv. An algorithm for the estimation of effective and organ doses from KAP has been established in HSG procedures depending on the Cu filtration in the X-ray irradiation events.